CA1 ensembles expressing immediate-early genes are driven by context switch, shrink with sustained presence, and show no effect of change of task demands - Krajcovic, Branislav; Cernotova, Daniela; Buchtova, Helena; Stuchlik, Ales; Kubik, Stepan; Svoboda, Jan (Behavioural brain research, 2025)
The hippocampus (HPC) is essential for navigation and memory, tracking environmental continuity and change, including navigation relative to moving targets. CA1 ensembles expressing immediate-early gene (IEG) Arc and Homer1a RNA are contextually specific. While IEG expression correlates with HPC-dependent task demands, the effects of behavioral demands on IEG-expressing ensembles remain unclear. In three experiments, we investigated the effects of context switch, sustained presence, and task demands on dorso-proximal CA1 IEG+ ensembles in rats. Experiment 1 showed that the size of IEG+ (Arc, Homer1a RNA) ensembles dropped to baseline during uninterrupted 30-min exploration, reflecting familiarization, unless a context switch was present. Context-specificity of the ensembles depended on both environment identity and timing of the context switch. Experiment 2 found no effect of HPC-dependent mobile robot avoidance or HPC-independent avoidance of a stationary robot on IEG+ ensembles beyond mere exploration. Experiment 3 replicated these findings for c-Fos protein. The data suggest that IEG+ ensembles are driven by a context switch and shrink over time during sustained presence in the same environment. We found no evidence of task demands or their change affecting the size, stability over time, or task-specificity of IEG+ ensembles. These results shed light on the temporal dynamics of CA1 IEG+ ensembles, and their control by contextual and behavioral factors.
Keywords: proteiny nervové tkáně; Behavioral episode; Ensemble stability; chování zvířat; RNA; Moving/stationary robot avoidance; Nerve Tissue Proteins; CA1 Region, Hippocampal; hipokampální oblast CA1; krysa rodu Rattus; Homer Scaffolding Proteins; Homer scaffold proteiny; zvířata; Rats, Long-Evans; C-Fos; Cytoskeletal Proteins; cytoskeletální proteiny; Male; Arc/Homer1a catFISH; Genes, Immediate-Early; potkani Long-Evans; Rats; okamžité časné geny; Animals; mužské pohlaví; Behavior, Animal